2019
DOI: 10.3390/catal9090720
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Encapsulated Pt Nanoparticles Dispersed in Low Temperature Oxygen for Partial Oxidation of Methane to Syngas

Abstract: Highly dispersed ultra-small Pt nanoparticles limited in nanosized silicalite-1 zeolite were prepared by in situ encapsulation strategy using H2PtCl6·6H2O as a precursor and tetrapropylammonium hydroxide as a template. The prepared Pt@S-1 catalyst was characterized by X-ray diffraction (XRD), inductively coupled plasma (ICP), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), N2 adsorption-desorption, CO adsorption, and TGA techniques and exhibited unmatched catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Various effective methods have been explored recently to reduce the size of metals to a certain extent, such as alkali metal addition, 68 two-step hydrothermal methods including low-temperature nucleation and high-temperature growth, 57 a combination of mother liquor aging and low temperature crystallization, 69 rational control of the calcination and reduction program 70 and further low-temperature oxygen calcination. 71 Wang et al 66 introduced KOH into the hydrothermal synthesis of ethylenediamine-stabilized Pd, and found that the size of Pd clusters decreased from 1.8 nm to 0.3 nm. The high-resolution scanning transmission electron microscopy (HRSTEM) in Fig.…”
Section: Direct Hydrothermal Synthesis For Metal@zeolite Catalystsmentioning
confidence: 99%
“…Various effective methods have been explored recently to reduce the size of metals to a certain extent, such as alkali metal addition, 68 two-step hydrothermal methods including low-temperature nucleation and high-temperature growth, 57 a combination of mother liquor aging and low temperature crystallization, 69 rational control of the calcination and reduction program 70 and further low-temperature oxygen calcination. 71 Wang et al 66 introduced KOH into the hydrothermal synthesis of ethylenediamine-stabilized Pd, and found that the size of Pd clusters decreased from 1.8 nm to 0.3 nm. The high-resolution scanning transmission electron microscopy (HRSTEM) in Fig.…”
Section: Direct Hydrothermal Synthesis For Metal@zeolite Catalystsmentioning
confidence: 99%
“…However, since its one-dimensional structure is not conducive to product diffusion, KL zeolite is susceptible to pore blockage by deposited coke, which results in a short catalyst lifetime and thus restricts further industrial applications to some extent. , For comparison, silicalite-1 (Sil-1) zeolite is an aluminum-free crystalline silicate with a three-dimensional pore structure, which has the same MFI topologic framework as the Al-containing ZSM-5 zeolite. Recently, many efforts have been implemented to reduce the size of metal particles and improve the catalytic stability by encapsulation of metal within Sil-1 zeolite. Wang et al prepared well-dispersed and ultrasmall Pd clusters in nanosized Sil-1 zeolite by an in situ hydrothermal synthesis method and exhibited superior catalytic activities for hydrogen generation via formic acid decomposition. Moreover, Sil-1 zeolite is regarded as chemically inert support, which has a positive effect on the selectivity of propylene.…”
Section: Introductionmentioning
confidence: 99%
“…Partial oxidation of methane (POM) is also one of the most powerful processes for syngas production, but the noble metal-based catalysts used in the process limit its research and application. In order to increase the atomic utilization of noble metals and solve the stability problem of nanoparticle-based catalysts, Wang et al [4] have proposed the encapsulation of noble metal nanoparticles as a way to develop catalogs with improved activity and stability in the partial oxidation of methane to syngas. The authors prepared Pt nanoparticles confined in silicalite-1 (S-1) zeolite under hydrothermal conditions and, strikingly, the combination of Pt nanoparticles and zeolite micropores, which limited their agglomeration during the reaction, led to enhanced catalytic activity and stability in POM, which was of great importance in increasing metal utilization and reducing catalyst costs.…”
mentioning
confidence: 99%
“…The adsorption competition mechanism of gas molecules (H 2 , H 2 O, CO, CH 4 , and H 2 ) on CaO-based catalysts was studied using density functional theory (DFT). The results indicated that the adsorption capacity of CO 2 on the surface of CaO-based catalysts surface was strongest at 650 • C. Furthermore, the adsorption competition mechanism of gas molecules was investigated by the DFT method, demonstrating that, in contrast with a CaO surface, a 10 wt % Ni/CaO surface is conducive for in situ CO 2 capture in biomass pyrolysis.…”
mentioning
confidence: 99%